The Crisis of Party Action in Morocco and the Challenge of Fostering Development: An Analytical Study - Ramdani, Fath Ellah (Journal of Humanities & Social Sciences, 2025)
This study aims to analyze the impact of the crisis of party action in Morocco on the process of fostering development by examining the essential roles played by political parties in supporting and ensuring the effectiveness of development strategies. The research is based on the assumption that the party action crisis, characterized by structural dysfunctions and weak political mobilization, directly undermines the effectiveness of development policies. A descriptive-analytical methodology was adopted, employing content analysis and historical approaches to trace the evolution of the partisan phenomenon, interpret the manifestations of the crisis, and assess its effects. The findings reveal that the widening gap between citizens and politics, along with declining trust and political participation, constitutes one of the most significant obstacles to democratization and development. Furthermore, the limited performance of political parties in designing and implementing public policies contributes to the ineffectiveness of development programs. The study recommends restructuring Moroccan political parties and enhancing their organizational and mobilization capacities to become key actors in consolidating democracy and advancing sustainable development.